Pendidikan bagi Perempuan Indonesia : Perjuangan Raden Dewi Sartika dan Siti Rohana Kudus (1904-1928) - Irfan Agung Jayudha; Wawan Darmawan (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2020)
The research discussed the roles between Raden Dewi Sartika and Siti Rohana Kudus strived for women’s education in Indonesia with the period of 1904-1928. The research background highlights Raden Dewi Sartika and Siti Rohana Kudus’ different thoughts and practices, in contrast to women in general at that time. Both of them lived in the same period, yet separated in distinctive regions. The main problem raised is how did Raden Dewi Sartika and Siti Rohana Kudus’s role in striving for women’s education. The method used in this study is a historical method using four steps of research such as heuristics, criticism, interpretation, and historiography, and data collection utilized literature study. Based on the results, it can be explained that Raden Dewi Sartika and Siti Rohana Kudus have similarities and differences. The two similarities were in their desire to elevate women’s level through education. Thus they strive for women’s education by establishing schools as well as actively participating in the national movement. And the solid foundation for both of them was to be a good mother to their children. However, Raden Dewi Sartika and Siti Rohana Kudus played different roles in the national movement and in the projected graduates from the schools that were both established